2009
DOI: 10.1007/10_2008_18
|View full text |Cite
|
Sign up to set email alerts
|

Use of Orbital Shaken Disposable Bioreactors for Mammalian Cell Cultures from the Milliliter-Scale to the 1,000-Liter Scale

Abstract: Driven by the commercial success of recombinant biopharmaceuticals, there is an increasing demand for novel mammalian cell culture bioreactor systems for the rapid production of biologicals that require mammalian protein processing. Recently, orbitally shaken bioreactors at scales from 50 mL to 1,000 L have been explored for the cultivation of mammalian cells and are considered to be attractive alternatives to conventional stirred-tank bioreactors because of increased flexibility and reduced costs. Adequate ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 31 publications
1
53
0
Order By: Relevance
“…Several studies have proven the suitability of TubeSpin Ò bioreactors for the cultivation of mammalian [16,[91][92][93] and insect cells [94,95] up to a scale of 50 mL. De Jesus et al showed the advantages offered by TubeSpin bioreactors 50 for process development with CHO cell cultures [91].…”
Section: Microalgae Cultivation In Tubespin ò Flasksmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have proven the suitability of TubeSpin Ò bioreactors for the cultivation of mammalian [16,[91][92][93] and insect cells [94,95] up to a scale of 50 mL. De Jesus et al showed the advantages offered by TubeSpin bioreactors 50 for process development with CHO cell cultures [91].…”
Section: Microalgae Cultivation In Tubespin ò Flasksmentioning
confidence: 99%
“…No oxygen limitations were observed, and CO 2 was stripped because of the large interface in the headspace. Zhang et al [16] demonstrated that it was possible to conduct parallel cultivations in TubeSpin bioreactors 50 and measured k L a values of up to 45 h -1 . Strnad et al [92] applied a D-optimal design approach in order to optimize process parameters for the cultivation of CHO cells in a TubeSpin bioreactor 50.…”
Section: Microalgae Cultivation In Tubespin ò Flasksmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we can model them using the Navier-Stokes equations: r u l D 0 in liquid (4) where u a and u l represent the velocity of the gas and the liquid, p a and p l their pressure, a and l their density and a and l their viscosity. T.u, pI / D .ru C ru T / pI is the Cauchy stress tensor and f a and f l represent the forces acting on the gas and the liquid.…”
Section: Setting and Definition Of The Problemmentioning
confidence: 99%